Functionalized bis(thiosemicarbazonato) complexes of zinc and copper: Synthetic platforms toward site-specific radiopharmaceuticals - Holland, J; Aigbirhio, F; Betts, H; Bonnitcha, P; Burke, P; Christlieb, M; Churchill, G; Cowley, A; Dilworth, JR; Donnelly, P; Green, J; Peach, J; et al. (2007)
Two new types of unsymmetrical bis(thiosemicarbazone) proligands and their neutral zinc(II) and copper(II) complexes have been synthesized. These bifunctional ligands both chelate the metal ions and provide pendent amino groups that can be readily functionalized with biologically active molecules. Functionalization has been demonstrated by the synthesis of three water-soluble glucose conjugates of the new zinc(II) bis(thiosemicarbazonato) complexes, and their copper(II) analogues have been prepared in aqueous solution via transmetalation. A range of techniques including NMR, electron paramagnetic resonance, cyclic voltammetry, high-performance liquid chromatography (HPLC), UV/vis, and fluorescence emission spectroscopy have been used to characterize the complexes. Four compounds, including two zinc(II) complexes, have been characterized by X-ray crystallography. The connectivity and conformation of the glucose conjugates have been assigned by NMR spectroscopy. Time-dependent density functional theory calculations have been used to assign the electronic transitions of the copper(II) bis(thiosemicarbazonato) chromophore. Two copper-64-radiolabeled complexes, including one glucose conjugate, have been prepared and characterized using radio-HPLC, and transmetalation is shown to be a viable method for radiolabeling compounds with copper radionuclides. Preliminary cell washout studies have been performed under normoxic conditions, and the uptake and intracellular distribution have been studied using confocal fluorescence microscopy. © 2007 American Chemical Society.